CCl4‐Enhanced Ultrasonic Irradiation for Ciprofloxacin Degradation and Antibiotic Activity: Wei et al. (1st July 2018) - Wei, Hong; Shi, Jingzhuan; Yang, Xiaoyu; Wang, Jiawei; Li, Kebin; He, Qiang
ABSTRACT: : In this study, an ultrasound/CCl4 system was used to degrade the fluoroquinolone antibiotic, ciprofloxacin, in aqueous solution. The effect of CCl4 concentration and initial solution pH on ciprofloxacin degradation were investigated. The results showed that ciprofloxacin degraded effectively under an ultrasound/CCl4 system, with degradation efficiency increasing from 0.51% to 50.92%, when the CCl4 concentration ranged from 0.0 to 41.4 mmol/L in 40 min. Radical scavenging experiments certified that both OH and chlorine‐containing radicals contributed to ciprofloxacin degradation. Eight intermediates were detected using ultra high‐performance liquid chromatography‐mass spectrometry (UHPLC‐MS) method, including three chloro‐intermediates. Based on these results, the possible degradation pathways of ciprofloxacin are proposed. Agar diffusion tests with E. coli and S. aureus showed that ciprofloxacin's antibacterial activity was completely removed in 40 min. This study indicates that an ultrasound/CCl4 system can degrade ciprofloxacin and remove its antibacterial activity, and thus is a promising process for treating fluoroquinolone antibiotics in wastewater.